Interaction among foreign direct investment, economic growth and foreign trade: evidence from India and China. (1st January 2014) - Chadha, Suresh K.; Singh, Bulbul; Natarajan, Vivek S.
During the past decade, the subject of FDI and economic growth has invited tremendous academic interest but there has been controversy over its causal relationship. This study investigates the multivariate causal relationship between FDI, economic growth and foreign trade in two of the fastest growing economies of the world, India and China. The vector error correction model was applied to examine the stability and interrelationships between the variables. Both countries have presented converse results as far as the causal relationship between FDI and GDP is concerned. In India, GDP Granger causes FDI; in China, FDI Granger causes GDP.